Nursing Students’ Perceptions of Project-Based Learning to Enhance English Proficiency: A Descriptive Quantitative Study: Persepsi Mahasiswa Keperawatan tentang Pembelajaran Berbasis Proyek untuk Meningkatkan Kemampuan Bahasa Inggris: Studi Kuantitatif Deskriptif - Kurnihayati, Kurnihayati; Solihin, Rully Khoeru; Muhria, Lanlan (Journal of Society and Development, 2025)
In today’s globalized healthcare environment, English proficiency is essential for nursing professionals to access international resources, communicate across cultures, and deliver high-quality care. This study investigates nursing students’ perceptions of Project-Based Learning (PjBL) as a strategy to enhance English language skills within clinical and academic contexts. A descriptive quantitative study was conducted at the Nursing Department of Universitas Muhammadiyah Ahmad Dahlan Cirebon, involving 56 students enrolled in an English for Specific Purposes (ESP) course. Data were gathered through a Likert-scale questionnaire focusing on aspects such as motivation, inquiry, planning, and relevance to clinical practice. The findings indicate that students perceive PjBL as highly effective in connecting classroom English learning to real-world nursing tasks. Reported benefits include increased motivation, improved critical thinking, enhanced self-directed learning, and stronger professional communication. Students also expressed high engagement and satisfaction due to the authenticity and relevance of the tasks. The study concludes that integrating PjBL into ESP instruction for nursing students can significantly improve both language proficiency and clinical readiness. These results highlight the pedagogical value of PjBL in nursing education and suggest further research to examine its long-term effects on language retention and professional performance.